Humoral and cellular responses to spike of δ SARS-CoV-2 variant in vaccinated patients with immune-mediated inflammatory diseases. (August 2022) - Petrone, Linda; Picchianti-Diamanti, Andrea; Sebastiani, Gian Domenico; Aiello, Alessandra; Laganà, Bruno; Cuzzi, Gilda; Vanini, Valentina; Gualano, Gina; Grifoni, Alba; Ferraioli, Mario; Castilletti, Concetta; Meschi, Silvia; et al.
Highlights: The cellular response to δ SARS-CoV-2 variant is present in vaccinated patients with immune-mediated inflammatory disease (IMID) The cellular response magnitude to δ SARS-CoV-2 variant depend on the type of therapy The serological response was similar between the patients with IMID and the control group Abstract: Objectives: We assessed vaccination-induced antibody and cellular responses against spike from the ancestral strain and from the delta (δ) SARS-CoV-2 variant in patients with immune-mediated inflammatory diseases (IMIDs) on immunosuppressive therapy in comparison with immunocompetent subjects. Methods: We enrolled patients with IMID and immunocompetent subjects who completed the vaccination schedule within 4–6 months from the first dose. The interferon (IFN)-γ-response to spike peptides that were derived from the ancestral and the δ SARS-CoV-2 were measured by ELISA. Anti-Receptor Binding Domain IgG antibodies were also evaluated. Results: We enrolled 43 patients with IMID and nine immunocompetent subjects. No significant differences were found after comparing the specific immune response (IFN-γ) between patients with IMID and immunocompetent subjects to the ancestral (p = 0.36) or δ peptide pool (p = 0.51). Nevertheless, IFN-γ-specific responses to the ancestral or to the δ pools were reduced in subjects taking CTLA4-IgG or TNF-α inhibitors compared with subjects treated with IL-6 inhibitors or Disease Modifying Anti-Rheumatic Drugs. Regarding the antibody response, no significant differences were observed between patients with IMID and immunocompetent individuals. Conclusions: Cellular responses to δ SARS-CoV-2 variant remain largely intact in patients with IMID. However, the magnitude of these responses is dependent on the specific IMID immunosuppressive regimen. Serological response was also similar between the IMID and control groups. Graphical abstract: Image, graphical abstract